Spiral wrap using CFRP strip to strengthen TSPC column under compression - Muhamad Soffi, Manda; Mohd Ruzaimi, Mat Rejab; Nor Shaufina, Md Jaafar (Politeknik Kota Bharu, 2023)
This study investigates the compressive strength enhancement of TSPC column under spiral wrap orientation of CFRP strips in comparison with conventional transverse CFRP wrap on the TSPC circular column samples. The test samples were prepared by wrapping TSPC with 30 mm CFRP strip with 0.60 angular offsets from bottom and continuously wrapped until it reaches top of the TSPC column. The matrix employed was epoxy Sikadur 330-part A and B. Compression test was performed on unconfined TSPC (TSPC-UC), TSPC with transverse CFRP confinement (TSPC-CF) and TSPC with spiral CFRP strip confinement (TSPC-CS) with 1mm/ min of loading rate. The test results have revealed that the ultimate strengths are 59.19 MPa (TSPC-UC), 108.77 MPa (TSPC-CF) and 116.53 MPa (TSPC-CS). The corresponding compressive strain measured at ultimate compressive strength is 0.0300 (TSPC-UC), 0.0398 (TSPC-CF) and 0.0420 (TSPC-CS). Stress versus strain curve has shown that compared to TSPC-UC, TSPC-CF and TSPC-CS has provided strength enhancement and improvement of yield point indicate the confinement effect on the test samples. However, TSPC-CS has shown just little strength enhancement compared to TSPC-CF which reveals its incompatibility due to complexity of spiral wrap preparation process. Failure mode of TSPC-UC has shown shear crushing, TSPC-CF, delamination, and transverse fractured and TSPC-CS exhibit angular fractured. The results of this study have provided findings on the effect of spiral CFRP strip confinement on TSPC circular column sample in close expectation based on literature.